DNA adducts of aristolochic acid II: total synthesis and site-specific mutagenesis studies in mammalian cells - Attaluri, Sivaprasad (Oxford University Press, 2010)
Aristolochic acids I and II (AA-I, AA-II) are found in all Aristolochia species. Ingestion of these acids either in the form of herbal remedies or as contaminated wheat flour causes a dose-dependent chronic kidney failure characterized by renal tubulointerstitial fibrosis. In ∼50% of these cases, the condition is accompanied by an upper urinary tract malignancy. The disease is now termed aristolochic acid nephropathy (AAN). AA-I is largely responsible for the nephrotoxicity while both AA-I and AA-II are genotoxic. DNA adducts derived from AA-I and AA-II have been isolated from renal tissues of patients suffering from AAN. We describe the total synthesis, de novo, of the dA and dG adducts derived from AA-II, their incorporation site-specifically into DNA oligomers and the splicing of these modified oligomers into a plasmid construct followed by transfection into mouse embryonic fibroblasts. Analysis of the plasmid progeny revealed that both adducts blocked replication but were still partly processed by DNA polymerase(s). Although the majority of coding events involved insertion of correct nucleotides, substantial misincorporation of bases also was noted. The dA adduct is significantly more mutagenic than the dG adduct; both adducts give rise, almost exclusively, to misincorporation of dA, which leads to AL-II-dA→T and AL-II-dG→T transversions.